Discharge against medical advice from a Tehran emergency department. Issue 1 (8th February 2016) - Hadadi, Azar; Khashayar, Patricia; Karbakhsh, Mojgan; Vasheghani Farahani, Ali
Abstract : Purpose: – The purpose of this paper is to identify the main reasons for discharge against medical advice (DAMA) in the emergency department (ED) of a teaching hospital in Tehran, Iran. Design/methodology/approach: – This cross-sectional study was conducted on all the patients who left the ED of a referral teaching hospital against medical advice (AMA) in 2008. A questionnaire was filled out for each patient to determine the reasons behind patient leaving AMA. Findings: – In total, 12.8 percent of the patients left the hospital AMA. Dissatisfaction with being observed in the ED, having a feeling of recovery and hospital personnel encouraging patients to leave the hospital were the main reasons for leaving the hospital AMA. Practical implications: – Like many other centers, the results showed that poor communication skill and work overload were the main contributing factors to DAMA. The center managed to improve patient satisfaction and thus lowered DAMA rates following this study. Considering the similarities reported in the reports and that of other studies, it could be concluded that policy makers in other centers can also benefit from the results to adopt effective approaches to reduce DAMA rate. Originality/value: – To the knowledge no study has evaluated the rate and the reasons behind DAMA in the Iranian EDs.